Production upgrading and skills development in the Western Cape clothing sector: are industry requirements being met by institutional policy implications? - Christie, Zara Danielle (School of Economics, 2017)
This research paper presents an overview and analysis of skills development in the Western Cape clothing sector in the context of production upgrading. The analysis touches on the broader South African skills development framework and industrial policy towards the clothing sector, notably the shift from mass production towards the adoption of Lean Production and the Quick Response retail model. As clothing firms based in the Western Cape evolved their production strategies and moved up the value-chain and towards Lean Production methods and Quick Response capabilities, skills requirements also evolved. As such, suitable skills development initiatives are required to support this evolution and industry innovation. Skills development institutions such as SETAs are unable to provide the necessary training required by these firms to successfully transition to the new production methods and retail supply model, with skills gaps and shortages occurring both at a technical and managerial level. Due to publicly funded institutions not providing the required associated training, a number of manufacturing firms are privately funding training programmes for their workers in an attempt to resolve this problem, but many cannot afford this intervention. While privately provided skills training may be a short-term transitional solution, it is not sustainable to ensure overall industry development, growth and success as firms undertake the implementation of evolved production methodologies and implement the Quick Response retail model.